Smart laser for blind people / Muhammad Haris Adlan Mohamad Nazri … [et al.] - Mohamad Nazri, Muhammad Haris Adlan; Azahari, Muhammad Hakimi; Azis, Siti Noraziana; Naseri, Roszi Naszariah Nasni (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Blind people often explore various aspects of their lives, including education, employment, social inclusion, and technology. Smart Laser is dedicated to address the needs of blind people. It discusses our company's products to enhance the lives of blind people, such as assistive technologies, accessibility solutions, or employment programs. It also may cover the values and impact on the blind community, as well as its efforts to promote inclusion, equality, and empowerment for blind people.